KETAHANAN PANGAN ANGGOTA DAN NONANGGOTA KWT MEKAR JAYA PENERIMA PROGRAM PEKARANGAN PANGAN LESTARI SELAMA PANDEMI COVID-19 - Rendi Setiawan; Yaktiworo Indriani; Maya Riantini (Jurnal Ilmu-Ilmu Agribisnis, 2023)
Goals of this study is to analyze food security and factors influencing food security of members and nonmembers of KWT Mekar Jaya, the recipient of the sustainable food yard program (P2L). This study was conducted purposively in Giri Tunggal Village of Pagelaran Utara Subdistrict of Pringsewu Regency.  There were 60 household samples consisting of 30 members and 30 nonmembers of KWT Mekar Jaya.  The main and second data of this research was collected in April-July 2021.  The first aim was analyzed by crosstabs between the part of food expenditure and sufficiency of energy and the second goal was analyzed by logistic regression.  The results of this study showed that most respondents (65%) are classified as food resistant, and the rest (35%) are classified as vulnerable to food. The factors that influenced the household food security were the number of family members and household income. Key words: food security, household, KWT Mekar Jaya, P2L